Bağlanma Stilleri Ve Yalnızlık Düzeylerinin Üniversite Öğrencilerinin İnternet Bağımlılığı Üzerindeki Yordayıcı Etkisinin İncelenmesi - Kılıçoğlu, Emine Arslan; Aral, Neriman (Bartın Üniversitesi, 2024)
the study aims to examine the predictive effects of attachment styles and loneliness levels of male university students on internet addiction. The study was conducted with male students attending universities in Konya, and 354 male students (61.6% associate degree, 38.4% undergraduate) attending universities in Konya who wanted to participate in the study were included. Research data were collected with a general information form, Young internet addiction scale, three-dimensional attachment scale, and UCLA loneliness scale. The data obtained in the research were analyzed using the SPSS (Statistical Package for Social Sciences) program. According to the research results, there is a positive and low level relationship (p
Examination of the Predictive Effect of Attachment Styles and Loneliness Levels on Internet Addiction of University Students
Keywords: Child Development Education; Çocuk Gelişimi Eğitimi